Nonmedical Management of Late Luteal Phase Dysphoric Disorder : A Preliminary Report - PEARLSTEIN, TERI (American Psychiatric Press, Inc, 1992)
The authors report the results of an open trial of group behavioral treatment for women with a prospectively confirmed premenstrual syndrome. Treatment consisted of five weekly group behavioral sessions outlining and supporting lifestyle changes in diet, exercise level, and stress management. Patients monitored symptoms and adherence to dietary and exercise recommendations daily. Results are discussed for the first 48 women to complete the trial. Eighty-three percent of patients demonstrated either a remission (n= 28) or 50% reduction in symptoms (n = 12) at one month following the group treatment. Improvements in physical and emotional symptoms were significantly associated with an increase in exercise.